2010
DOI: 10.4317/medoral.15.e677
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic treatment in the oral cavity: An update

Abstract: Probiotics have been found to be beneficial to host health. Their primary use in medicine has been for the management of intestinal tract problems. In recent years, probiotics have been used as a treatment to promote oral health. The aim of the present study was to review published studies regarding probiotics and their effects on the oral cavity. Studies reporting the anticariogenic effects of probiotics, their use in the treatment of periodontal disease, a reduced crevicular fluid volume and cytokine content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 21 publications
0
32
0
3
Order By: Relevance
“…Results obtained by Koll et al, when assessing the effects of various Lactobacillus strains in oral cavity were markedly different; most strains suppressed growth of periodontal pathogens, including A. actinomycetemcomitans (60 out of 67 tested strains); P. gingivalis (35 out of 42 strains); P. intermedia (26 out of 42 strains); and carcinogenic S. mutans (37 out of 67 strains). No inhibition was found for C. albicans growth (Flichy-Fernández AJ et al, 2010). The authors had no explanation to this and the finding certainly needs to be confirmed in further investigations.…”
Section: Probiotics In Oral Health and Diseasementioning
confidence: 71%
“…Results obtained by Koll et al, when assessing the effects of various Lactobacillus strains in oral cavity were markedly different; most strains suppressed growth of periodontal pathogens, including A. actinomycetemcomitans (60 out of 67 tested strains); P. gingivalis (35 out of 42 strains); P. intermedia (26 out of 42 strains); and carcinogenic S. mutans (37 out of 67 strains). No inhibition was found for C. albicans growth (Flichy-Fernández AJ et al, 2010). The authors had no explanation to this and the finding certainly needs to be confirmed in further investigations.…”
Section: Probiotics In Oral Health and Diseasementioning
confidence: 71%
“…It also decreased Streptococcus mutans count in saliva of orthodontic adolescents and long term intake prevented sore throat in childrens. Weissella confusa isolates and microorganisms forming lactic acid also appear to decrease halitosis 22,23,26,29,31,34,47 .…”
Section: Halitosismentioning
confidence: 99%
“…The areas of their medical therapeutics include heart diseases, allergic reaction, irritable bowel syndrome, reduction of liver toxicities, hypertension, urogenital health, respiratory tract infections, infections with Helicobacter pylori, optimize effects of vaccines, etc 24,27,29,32,35 .…”
Section: Therapeutic Actions Of Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably intestinal bacteria may regulate body weight by affecting the host's metabolic neuroendocrine and immune functions [80]. Additionally, probiotics may have anticariogenic effects, preventing and treating dental caries and generally be effective in the oral cavity and the treatment of periodontal disease [81,82].…”
Section: Other Disordersmentioning
confidence: 99%